Empowering The Use Of Vocabulary Card In Students At Adameesuksavittaya School Krabi Thailand To Improve Vocabulary In Arabic Language Mastery - Muffti, Arif; Salam, Muhammad Yusuf; Kiat, Tom (Yayasan Pendidikan Islam Daarut Thufulah, 2025)
Background. Vocabulary limitations were identified as a major barrier to students' communication skills and language learning.Purpose. To improve students' vocabulary mastery at Adameesuksavittaya School, Krabi, Thailand, with a focus on Arabic language mastery. Vocabulary limitations were identified as a major barrier to students' communication skills and language learning. Method. With a qualitative case study approach, vocabulary cards were applied as a supplementary learning method. Data were collected through direct observation, interviews, and questionnaires to assess the effectiveness of this method.Results. The results showed significant improvements in vocabulary mastery, student engagement in learning, and students' confidence in using Arabic. Vocabulary cards were not only effective in classroom learning but also supported language use in daily interactions. Teachers and students gave positive responses, with this method creating a more interesting and interactive learning atmosphere.Conclusion. This study concludes that vocabulary cards are an effective tool to improve students' vocabulary mastery and communication skills, and recommends its use in other educational settings. Further research is recommended to explore the application of this method in various educational contexts.